Observation of Ω(2012)−→Ξ(1530)K¯ and measurement of the effective couplings of Ω(2012)− to Ξ(1530)K¯ and ΞK¯ - S. Jia; C.P. Shen; C.Z. Yuan; J.K. Ahn; H. Aihara; D.M. Asner; H. Atmacan; R. Ayad; S. Bahinipati; Sw. Banerjee; J. Bennett; M. Bessner; et al. (Physics Letters B)
Using ϒ(1S), ϒ(2S), and ϒ(3S) data collected by the Belle detector, we discover a new three-body decay, Ω(2012)−→Ξ(1530)K¯→ΞπK¯, with a significance of 5.2 σ. The mass of the Ω(2012)− is (2012.5±0.7±0.5) MeV and its effective couplings to Ξ(1530)K¯ and ΞK¯ are (39−39+31±9)×10−2 and (1.7±0.3±0.3)×10−2, where the first uncertainties are statistical and the second are systematic. The ratio of the branching fraction for the three-body decay to that for the two-body decay to ΞK¯ is 0.99±0.26±0.06, assuming isospin symmetry.